MODIFIKASI ALAT PENGERING ENERGI SURYA TIPE RAK UNTUK PENGERINGAN BAHAN PANGAN - Noviset Tumbal; Daniel P.M. Ludong; Lady C. Ch. E. Lengkey (Universitas Sam Ratulangi, 2022)
ABSTRACT This study aims to modify a racks-type dryer with a combination of electrical energy and sunlight and to design a heat distribution system for the 3 (three) drying racks to be uniform and the drying temperature can be maintained optimally. This study uses an experimental design method with a trial and error form. The implementation of this research includes the stages of modification, testing, as well as observation and data processing (temperature and humidity). After the dryer was modified, an experiment was carried out to dry the cayenne pepper. The result of the modification of a shelf-type solar dryer consists of several main components, namely a drying chamber, solar collector, and heating/electric element with dimensions of a rectangular drying chamber measuring 100 cm long, 60 cm wide, and 120 cm high, as well as a solar collector. measuring 215 cm long, 125 cm wide at the bottom, 50 cm wide at the top, and 16 cm thick. The experimental results obtained, namely the highest average temperature on each shelf, namely the top shelf 69.80 oC, the middle shelf 66.10 Â°C, and the bottom shelf 57Â°C. while the lowest RH on each shelf is the top shelf 11.50%, the middle shelf 14.30% and the bottom shelf 21.30%.